(untitled) (Scientific journal of the Fergana State University, 2025)
The scientific literature on the theoretical basis of possible differences in the reaction of men and women to physical overload in conditions with different environmental temperatures has been analyzed, studying the importance of territorial factors in the reaction of the female organism to physical exercise.